Is cognitive impairment associated with reduced syntactic complexity in writing? Evidence from automated text analysis - Sand Aronsson, Fredrik; Kuhlmann, Marco; Jelic, Vesna; Östberg, Per (Aphasiology, 2021)
Background: Written language impairments are common in Alzheimer's disease and reduced syntactic complexity in written discourse has been observed decades before the onset of dementia. The validity of average dependency distance (ADD), a measure of syntactic complexity, in cognitive decline needs to be studied further to evaluate its clinical relevance. Aims: The aim of the study was to determine whether ADD is associated with levels of cognitive impairment in memory clinic patients. Methods & procedures: We analyzed written texts collected in clinical practice from 114 participants with subjective cognitive impairment, mild cognitive impairment, and Alzheimer's disease during routine assessment at a memory clinic. ADD was measured using automated analysis methods consisting of a syntactic parser and a part-of-speech tagger. Outcomes & results: Our results show a significant association between ADD and levels of cognitive impairment, using ordinal logistic regression models. Conclusion: These results suggest that ADD is clinically relevant with regard to levels of cognitive impairment and indicate a diagnostic potential for ADD in cognitive assessment.